Analisis Kepercayaan Diri Pada Korban Bullying - Syahra, Milani Nabila; Putri, Kania Annisa; Setiawan, Thalia Amelinda (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Bullying is a problem that is always discussed. Because bullying cases are still widespread in Indonesia, especially during adolescence. Adolescence is a time when a child still has great curiosity and without guidance and good parenting from parents, behaviors will emerge that will ultimately have an impact on the environment and themselves. The aim of this research is to determine the effect of bullying on teenagers' self-confidence by using quantitative research methods, namely a literature study design, where the data presented by the researcher is the result of previous research analysis. To reveal cases of problems that often arise which can later be followed up. The results of the literature study that we analyzed showed a significant influence on the very low self-confidence of bullying victims. And a child who is a victim of bullying can experience learning disorders in his academic activities. So you have to involve them in positive activities and provide love and trust which includes the perpetrators and victims of bullying and gives them an understanding of the negative impacts of bullying. For this reason, there needs to be participation between schools, teachers and guardians to overcome bullying against children. One researcher also stated that directive counseling is very effective in overcoming low self-confidence behavior.